HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN MOTIVASI BELAJAR PADA MAHASISWA - Basri Basri (Jurnal Sosial Humaniora Sigli, 2020)
This study aims to determine the relationship between emotional intelligence with learning motivation in students and counseling Jabal Ghafur University. This research uses Pearson product Moment analysis technique with sampling technique using Purposive Sampling. The subjects of the study were counseling students of Jabal Ghafur University with a sample of 79 students. Based on the results of data analysis shows there is a very significant positive relationship between emotional intelligence with learning motivation, where rxy = 0.555; p = 0,000 (p [0.050). The result of the research shows that the prospect of counseling of Jabal Ghafur University has high emotional intelligence, because the empirical average value is 97,354 difference with the average hypothetical value of 77,5 over SD or SB number of 8, 184, while the students' learning motivation is high because empirical 135, 658 in the presence of a hypothetical average value of 110 to the number of SD or SB amounted to 11, 613. Keywords: Learning Motivation, Emotional Intelligence, Guidance and Counseling students.